Membangun Generasi Berintegritas Pendidikan Karakter dalam Kurikulum Nasional di Sekolah Dasar - Hotmian Situmorang; Indri Anggraini; Cut Kumala Sari (Asosiasi Riset Ilmu Pendidikan Indonesia, 2025)
With an emphasis on two key values responsibility and creativity this study attempts to evaluate how character education implementation shapes students' integrity at SDN 2 Karang Anyar. Data were gathered through documentation studies, teacher and principal interviews, and observation using a qualitative methodology.